Thymic microenvironmental alterations in experimentally induced diabetes - Nagib, Patricia R. A.; Gameiro, Jacy; Stivanin-Silva, Luiz Guilherme; Arruda, Maria Sueli Parreira de [UNESP]; Serra Villa-Verde, Dea Maria; Savino, Wilson; Verinaud, Liana (Elsevier Gmbh, Urban & Fischer Verlag, 2010)
Little is known about the immunologic consequences from endocrine changes observed in diabetes. Since a preserved thymic microenvironment is of critical importance for the T cell development and maturation, we have examined the thymus from alloxan-diabetic mice. An intense thymic atrophy accompanied by changes in histological pattern and in thymocyte subpopulations were observed in diabetic mice. Laminin and fibronectin, which are closely associated with thymocytes maturation, were evaluated, but, only laminin presented an altered distribution and density in thymuses from diabetes group. the expression of fibronectin and laminin receptors was found to be decreased in diabetic mice. There was also intense decrease in the expression of two important chemokines for thymus, CCL25 and CXCL12, and in the CCR9 (CCL25 receptor), but the expression of CXCR4 (CXCL12 receptor) did not drop on cells. However, no significant difference was observed in the in vitro thymocytes migratory capacity from diabetic mice. The results show significant alterations in thymus microenvironment in diabetes and offer insights for studies involving endocrine influences on lymphatic organs and T cell maturation. (C) 2010 Elsevier GmbH. All rights reserved.
Keywords: Thymus; Thymic microenvironment; Diabetes; Extracellular matrix; Chemokines